Correction: Duma et al. Death by Frostbite: From Theory to Reality: A Case Report. Forensic Sci. 2024, 4, 555–565 - Stefano Duma; Federica Mele; Mariagrazia Calvano; Mirko Leonardelli; Enrica Macorano; Giovanni De Gabriele; Alessandro Cristalli; Andrea Marzullo; Francesco Introna (Forensic Sciences, 2025)
In the original publication [...]